Hydrogenative Cyclopropanation and Hydrogenative Metathesis. Issue 26 (17th May 2019) - Peil, Sebastian; Guthertz, Alexandre; Biberger, Tobias; Fürstner, Alois
Abstract: The unusual geminal hydrogenation of a propargyl alcohol derivative with [Cp X RuCl] as the catalyst entails formation of pianostool ruthenium carbenes in the first place; these reactive intermediates can be intercepted with tethered alkenes to give either cyclopropanes or cyclic olefins as the result of a formal metathesis event. The course of the reaction is critically dependent on the substitution pattern of the alkene trap. Abstract : Janus character : gem ‐Hydrogenation of propargyl alcohol derivatives provides a conceptually novel entry into metal carbene complexes. Specifically, the use of [Cp*RuCl]4 as catalyst affords pianostool ruthenium carbenes that engage in either cyclopropanation or metathetic ring closure; the outcome of the reaction is largely dictated by the substitution pattern of the chosen olefinic trap.